VARIASI INDEKS VEGETASI NDVI PADA PERUBAHAN LANSKAP LAHAN KOTA AMBON,PROVINSI MALUKU - Gun Mardiatmoko; Jusmy D. Putuhena; Rus'an Latuconsina (JURNAL HUTAN PULAU-PULAU KECIL, 2020)
The development of Ambon City has always been linear with urbanization and land use, where an increasing number of people have urged forest lands to be converted to open lands, such as settlements, businesses, and other infrastructure in the form of built-up land. On a larger scale, the process of land-use change results in land cover changes that affect changes in the Ambon City landscape and microclimate conditions. The biogeophysical characteristic cs of Ambon City as a small island region have a large and small river basin and hilly topography makes it risky when city development pays little attention to the balance of ecological landscape aspects. Therefore this study aims to analyze the variation of the vegetation index NDVI (Normalized Difference Vegetation Index) on changes in the Ambon City, Maluku Province. The results showed that during the last 25 years (1993 to 2018) there was an increase in class area from Very Rare Forest to Rare Forest by 874.04 ha, an increase in the class area of ​​Medium Forest by 567.42 ha, an increase in class area from Dense Forest to Very Dense by 2,861.80 ha and a decrease in class area from Dense Forest to Very Dense Forest by 4,176.07 ha. If the reduction in the classes size of Dense Forest and Very Dense Forest is combined into groups of class increase of Very Rare Forest and Rare Forest, then the total increase in the land landscape area with a reduced or lost vegetation value was 5,050.11 ha.